Pancasila Student Profile: Integrating Environmentalism and Sustainable Lifestyles in Schools - Adhani, Yuli; Panai, Dewi Nur Indah; Bahsoan, Agil; Mas, Sitti Roskina; Badu, Syamsu Qamar; Dilipanga, Muhammad Beni (Jambura Journal Civic Education, 2024)
This study aims to analyse the implementation of the Pancasila Student Profile (P5) strengthening project with the theme 'Sustainable Lifestyle' to apply environmental love in the Merdeka Belajar Curriculum at SMP Negeri 1 Bulawa. The Merdeka Belajar curriculum implemented in this school aims to develop 21st-century competencies through a learning approach that focuses on students' interests and talents. P5 is part of this curriculum which is expected to shape the character of students in accordance with the values of Pancasila. One of the themes chosen for P5 implementation is 'Sustainable Lifestyle', which aims to raise students' awareness of the importance of protecting the environment and managing waste. This research used a qualitative method with a case study approach at SMP Negeri 1 Bulawa. Data was collected through observation, interviews with the principal, teachers and students, and documentation related to the implementation of the P5 project. The results showed that although procedurally, the P5 project has been implemented substantially, the implementation has not fully achieved the expected goals. Some of the problems found during the implementation of the project include the lack of student awareness of the importance of waste management, low student participation in providing creative ideas, and the existence of behaviours that do not reflect an environmentally friendly attitude, such as littering.